(untitled) (Jurnal Proaksi, 2022)
Abstract Bank profitability is able to help banks to see their performance in a certain period. ROA’s bank had increased despite the Covid-19 pandemic. This increase shows that the bank’s performance is quite good. The purpose of this research is to analyze the factors that affect bank profitability. The variables used are bank size, operational efficiency, liquidity, CAR, and GDP with the dependent variable profitability including ROA and NIM. A sample of 39 banks on the Indonesia Stock Exchange for the 2017-2021 period that uses the panel data regression analysis method. The novelty of this study is adding the NIM variable. Research shows the results that bank size and GDP have a positive and significant effect on ROA and NIM. Meanwhile, CAR has a significant and negative effect on NIM. However, there is no influence from CAR and liquidity on ROA. Keywords: CAR, GDP, liquidity, profitability